SYSTEMATIC LITERATURE REVIEW OF THE IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM BASED ON MODERN TECHNOLOGY IN BUMDES CONTRIBUTES TOWARDS IMPROVING THE QUALITY OF FINANCIAL REPORTS IN TERMS OF ACCURACY, TRANSPARENCY AND ACCOUNTABILITY - Rosalena Belo Ratte; Haliah; Nirwana (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The purpose of this study is to explore the application of modern technology-based accounting information systems in BUMDes contributing to improving the quality of financial reports in terms of accuracy, transparency, and accountability at various organizational scales and types of businesses. The method used is Systematic Literature Review aimed at ensuring and evaluating the contribution of previous studies on the application of modern technology-based Accounting Information Systems in BUMDes Financial Reports. The assessment of the quality of the articles obtained includes the validity, reliability, and relevance of the research to the questions asked. In general, this study presents the importance of the application of modern technology-based accounting information systems to support BUMDes activities and accountability amidst increasingly tight business competition. Modern technology offers the right solution to help facilitate various jobs, one of which is the automation of Financial Reports.